STRATEGY FOR INCREASING THE INVESTMENT ATTRACTIVENESS OF THE AGRO-INDUSTRIAL COMPLEX - G.Zh. Abdykerova; D.M. Aikupesheva; Zh.A. Seitova (Academic Journal of Physical and Chemical Sciences, 2019)
The article is devoted to the analysis of problems of increasing the investment attractiveness of the AIC. The role of the government in the management of investment processes is disclosed. The main factors that hold the influx of investments and measures on increasing the investment attractiveness of the AIC are given. The principles of state-private partnership in the AIC to create optimal conditions of attracting private capital to the agroindustrial complex are discussed.